INFLUENCE OF ENVIRONMENTAL FACTORS ON THE ACADEMIC PERFORMANCE OF OFFICE TECHNOLOGY AND MANAGEMENT STUDENTS - Zubairu, Alfa Mohammed; Abubakar, Usman; Gana, Cecila F.; Abubakar, Idris Mohammed; Baiwa, Yahaya Mohammed (FUDMA Journal of Sciences, 2025)
This study examined the influence of environmental factors on the academic performance of office technology and management students. Environment in which a child receives his/her upbringing can make or mar his psyche, which in turn affects academic performance in one way or the other. The environment may generally be considered to be the home and the school climate. Hence, the study adopted descriptive survey research design. The population of the study comprised 150 students of ND1 levels in office technology and management, which formed the sample for the study as the researchers considered the population to be sizeable and manageable.A Structured questionnaire based on modified four point Likert rating scale of Strongly Agreed (4), Agreed (3), Disagreed (2) and Strongly Disagreed (1) was the instrument used for data collection. The instrument was validated by three experts in the field of Office Technology and Management, The Federal Polytechnic, Bida. The researchers administered 150 copies of the questionnaire to the respondents and retrieved only 123 copies representing 82% return rate.Mean and Standard Deviation were the statistical tools used to answer and analyze the data collected from the respondents.Based on the data analysis, findings revealed among others that; school location(Mean = 2.73 & SD = 0.89), facilities (Mean = 3.31 & SD = 0.62),positively influence academic performance of office technology and management students to a moderate extent in polytechnics in Niger state. It was concluded that location, facilitieshad influence on academic performance of office technology and management students in polytechnics in Niger state.
Keywords: Environmental Factors; OTM students; Academic Performance